Students Attitudes and Readiness to Study Together with People Disabilities in Higher College - Isa Bela Islami; Triyanto Pristiwaluyo; Joko Yuwono; Wizerti Ariastuti Saleh (International Inclusion Development and Cooperation, 2023)
The problems studied in this study were students attitudes and readiness to take part in education with persons with disabilities on campus. This research is aimed to find out the attitudes and readiness of students to take part in education with persons with disabilities on campus. The variables in this study were students attitudes towards persons with disabilities and their readinessto participate in education with persons with disabilities. Data collection was carried out using a questionnaire in the Google form format which was distributed to all Faculty of Education (FIP) students. The willingness of students to fill out the questionnaire was considered random. The number of students who filled out the questionnaire was 159 people. The data were processed using descriptive and correlation analysis techniques, with the help of the ready-to-use SPSS program. The results showed that all students had a positive attitude towards persons with disabilities, and overall there was no difference in attitudes towards persons with disabilities on campus between male and female students. Most of the students expressed their readiness to takepart in education with persons with disabilities on campus. Student attitudes have a positive and significant relationship with student readiness to participate in education for persons with disabilities on campus. The experience of interacting with persons with disabilities has a positive and significant effect on students attitudes toward persons with disabilities on campus.